Catheter ablation versus antiarrhythmic drugs with risk factor modification for treatment of atrial fibrillation: a protocol of a randomised controlled trial (PRAGUE-25 trial) - Stepan Havranek; Jiri Jarkovsky; Otakar Jiravský; Pavel Osmancik; Veronika Bulková; Jan Chovančík; Tomáš Roubíček; Dalibor Heřman; Zuzana Čarná; Vladimír Tuka; Martin Matoulek; Martin Fiala; et al. (BMJ Open)
Introduction Atrial fibrillation (AF), with a prevalence of 2%, is the most common cardiac arrhythmia. Catheter ablation (CA) has been documented to be superior to treatment by antiarrhythmic drugs (AADs) in terms of sinus rhythm maintenance. However, in obese patients, substantial weight loss was also associated with AF reduction. So far, no study has compared the modern non-invasive (AADs combined with risk factor modification (RFM)) approach with modern invasive (CA) treatment. The aim of the trial is to compare the efficacy of modern invasive (CA) and non-invasive (AADs with risk factor management) treatment of AF.Methods and analysis The trial will be a prospective, multicentre, randomised non-inferiority trial. Patients with symptomatic AF and a body mass index >30 will be enrolled and randomised to the CA or RFM arm (RFM+AAD) in a 1:1 ratio. In the CA arm, pulmonary vein isolation (in combination with additional lesion sets in non-paroxysmal patients) will be performed. For patients in the RFM+AAD arm, the aim will be a 10% weight loss over 6–12 months, increased physical fitness and a reduction in alcohol consumption. The primary endpoint will be an episode of AF or regular atrial tachycardia lasting >30 s. The secondary endpoints include AF burden, clinical endpoints associated with AF reoccurrence, changes in the quality of life assessed using dedicated questionnaires, changes in cardiorespiratory fitness and metabolic endpoints. An AF freedom of 65% in the RFM+AAD and of 60% in the CA is expected; therefore, 202 patients will be enrolled to achieve the non-inferiority with 80% power, 5% one-sided alpha and a non-inferiority margin of 12%.Ethics and dissemination The PRAGUE-25 trial will determine if modern non-invasive AF treatment strategies are non-inferior to CA. The study was approved by the Ethics Committee of the University Hospital Kralovske Vinohrady. Results of the study will be disseminated on scientific conferences and in peer-reviewed scientific journals. After the end of follow-up, data will be available upon request to principal investigator.Trial registration number ClinicalTrials.gov Registry (NCT04011800).